KLF2 Inhibits Chicken Preadipocyte Differentiation at Least in Part via Directly Repressing PPARγ Transcript Variant 1 Expression - Cui, Tingting; Huang, Jiaxin; Sun, Yingning; Ning, Bolin; Mu, Fang; You, Xin; Guo, Yaqi; Li, Hui; Wang, Ning (Frontiers in Cell and Developmental Biology, 2021)
Peroxisome proliferator-activated receptor gamma (PPARγ) is the master regulatory factor of preadipocyte differentiation. As a result of alternative splicing and alternative promoter usage, PPARγ gene generates multiple transcript variants encoding two protein isoforms. Krüppel-like factor 2 (KLF2) plays a negative role in preadipocyte differentiation. However, its underlying mechanism remains incompletely understood. Here, we demonstrated that KLF2 inhibited the P1 promoter activity of the chicken PPARγ gene. Bioinformatics analysis showed that the P1 promoter harbored a conserved putative KLF2 binding site, and mutation analysis showed that the KLF2 binding site was required for the KLF2-mediated transcription inhibition of the P1 promoter. ChIP, EMSA, and reporter gene assays showed that KLF2 could directly bind to the P1 promoter regardless of methylation status and reduced the P1 promoter activity. Consistently, histone modification analysis showed that H3K9me2 was enriched and H3K27ac was depleted in the P1 promoter upon KLF2 overexpression in ICP1 cells. Furthermore, gene expression analysis showed that KLF2 overexpression reduced the endogenous expression of PPARγ transcript variant 1 (PPARγ1), which is driven by the P1 promoter, in DF1 and ICP1 cells, and that the inhibition of ICP1 cell differentiation by KLF2 overexpression was accompanied by the downregulation of PPARγ1 expression. Taken together, our results demonstrated that KLF2 inhibits chicken preadipocyte differentiation at least inpart via direct downregulation of PPARγ1 expression.